Kemampuan Susu Fermentasi Lactobacillus plantarum Menghambat Salmonella typhymurium Secara In Vitro - Zuraida Hanum (Jurnal Agripet, 2010)
The ability of Lactobacillus plantarum fermented milk to inhibit Salmonella typhymurium in vitroABSTRACT. This research used Lactobacillus plantarum as a milk starter (concentration 3, 4, 5 %) and incubated for 48 hours at room temperature. Observation fermented begin from the first day of this product until 7 days and its still stored at room temperature. First analysis conducted on milk in this research were Storch, pH, acidity titration, fat, and dry matter. Milk fermentation analysis of Lactobcillus plantarum including pH, degree of dornik acidity and microbe activity test. Experimental design used is Repeated Measurement with three replications. Data colected analyzed by ANOVA test. If there is significant different between treatments, followed by Least Significant Test. Complete pasteurization result test (Storch) found that milk stay white, it means that peroksidase enzyme completely disappear and milk completely pasteurization. The ability of suppressing observed by Salmonella typhymurium in Nutrient Agar and challenge with Lactobacillus plantarum fermented milk 3%, 4% and 5% (50 l/well). Tetracyline, chloramphenicol and a plain paper disc are used as control. Lactobacillus plantarum fermented milk of starter concentration 5%-first day has the biggest inhabitation zone by Salmonella typhimurium (9.39 mm). Range of pH showed between 4.84 to 4.14 and the acidity between 114.67 0D to 365.67 0D. Sensitivity test showed that Salmonella typhymurium more sensitive than chloramphenicol and tetracyline antibiotic.